Biological control of cassava green mite with exotic and indigenous phytoseiid predators—effects of intraguild predation and supplementary food - Onzo, A.; Hanna, R.; Negloh, K.; Toko, M.; Sabelis, M.W. (Elsevier, 2005)
Intraguild predation, one aspect of predator–predator interaction, has received in recent years increasingly greater attention because of mounting evidence of the impact of predator–predator interactions on the structure of ecological communities and biological pest control. In laboratory experiments, we determined if intraguild predation occurs between Typhlodromalus manihoti and Euseius fustis, two phytoseiid mite predators of the cassava green mite Mononychellus tanajoa on cassava in Africa, and if the level of intraguild predation is affected by the availability of the primary prey, M. tanajoa, and maize pollen as alternative non-prey food. In the laboratory, the two predators attacked and killed heterospecific larvae but they did so only when prey mites and alternative food (maize pollen) were absent or scarce. On a diet of intraguild prey alone, the two predator species survived for several days but failed to reproduce. Addition of abundant levels of M. tanajoa and maize pollen increased survival and reproduction of the two predator species and reduced intraguild predation to very low levels. We then determined, on whole plants in pot experiments in a screenhouse, the effect of maize pollen (an alternative food) on the interactions between the two predator species and the impact of predator–predator interactions on suppression of M. tanajoa population densities. In single predator species treatments, both E. fustis and T. manihoti significantly reduced M. tanajoa densities; but surprisingly, E. fustis appeared to be superior to T. manihoti. The co-presence of the two predators on the same cassava plant resulted in similar suppression of M. tanajoa population densities, but greater suppression of M. tanajoa compared with T. manihoti alone, regardless of presence or absence of maize pollen. The presence of the two predator species together reduced their respective abundance compared with single predator species treatments. Addition of maize pollen, however, significantly increased densities of the generalist predator E. fustis, in both single and two predator species treatments; and tilted the balance of the interactions between the two predator species in favour of E. fustis. The findings of our research underscore the role of generalist predators like E. fustis in the suppression of M. tanajoa populations on cassava, and the potential role of alternative non-prey food in altering the interactions between co-occurring predators sharing the same primary prey (by favouring the generalist predators), and the effect of these interactions on suppression of population densities of the shared primary prey.